Technical Change and The Commons - Squires, Dale; Vestergaard, Niels (The Review of Economics and Statistics, 2013)
This paper addresses normative exploitation of common renewable resources with changes in technology and technical, allocative, and scale efficiency that exacerbate the commons problem and externality. Their impact depends on the rate and nature of change, investment, and state of property rights. An augmented fundamental equation of renewable resources with a modified marginal stock effect and a new marginal technology effect account for changes in disembodied and embodied technology and technical efficiency. Neglecting these changes generates misleading policy advice and dynamic inefficiency with overaccumulation of physical and natural capital and sizable foregone rents. An empirical application illustrates.